The Panel VAR Approach to Modelling the Housing Wealth Effect: Evidence from selected European post-transition economies - Čeh Časni, Anita; Dumičić, Ksenija; Tica, Josip (Naše gospodarstvo/Our economy, 2016)
Following Friedman’s permanent income hypothesis and Ando and Modigliani’s lifecycle hypothesis, this paper empirically studies the role of house prices and income in determining the dynamic behaviour of consumption in selected European post-transition economies using the panel vector autoregression (PVAR) approach and quarterly data covering the period from the first quarter of 2002 until the second quarter of 2012. With the shocks being recognized using the customary recursive identification scheme, we found that the response of personal consumption to the housing wealth shock is initially positive, but short lived.